Training Kit and Module on Plc Programming Competence for Students of Electrical Engineering Education - Puput Wanarti Rusimamto; Munoto Munoto; Muchlas Samani; I G.P. Asto Buditjahjanto; Endryansyah Endryansyah; Subuh Isnur Haryudo (Graduate School of Universitas Negeri Malang, 2021)
Abstract: This research aims to determine the validity and practicality of training kit and PLC learning module as an instructional media for PLC course for students of electrical engineering education at Universitas Negeri Surabaya. That was development research using Thiagarajan’s 4D models, this study only used the first three stages, not up to the disseminating stage, as the researcher only developed the training kit and module. The design of the training kit and module were developed and validated based on the look of the product, the quality of the media, and the suitability of the media for the curriculum and illustrations. The results of validation and trial process were used to determine the feasibility level of the module that had been developed in terms of validity and practicality. Findings showed that the training kit validation was valid at 85.18%, the module validation was valid at 83.33%. Another finding depicted that students’ responses showed that both the training kit and module were practical with percentages of 85% and 82.17% respectively. So that the training kit and PLC module were feasible to be used in PLC learning process by students of Electrical Engineering Education program at Universitas Negeri Surabaya.Abstrak: Penelitian ini bertujuan untuk mengetahui validitas dan kepraktisan training kit dan modul pembelajaran PLC sebagai media pembelajaran mata kuliah PLC bagi mahasiswa pendidikan teknik elektro Universitas Negeri Surabaya. Yaitu penelitian pengembangan menggunakan model 4D Thiagarajan, penelitian ini hanya menggunakan tiga tahap pertama, tidak sampai tahap diseminasi, karena peneliti hanya mengembangkan training kit dan modul. Perancangan perangkat pelatihan dan modul dikembangkan dan divalidasi berdasarkan tampilan produk, kualitas media, dan kesesuaian media untuk kurikulum dan ilustrasi. Hasil proses validasi dan uji coba digunakan untuk mengetahui tingkat kelayakan modul yang telah dikembangkan ditinjau dari validitas dan kepraktisan. Hasil penelitian menunjukkan validasi training kit valid sebesar 85,18%, validasi modul valid sebesar 83,33%. Temuan lain menunjukkan bahwa tanggapan siswa menunjukkan bahwa baik perangkat pelatihan maupun modul praktis dengan persentase masing-masing 85% dan 82,17%. Sehingga training kit dan modul PLC layak untuk digunakan dalam proses pembelajaran PLC oleh mahasiswa program studi Pendidikan Teknik Elektro Universitas Negeri Surabaya.